The impact of micropollutants on native algae and cyanobacteria communities in ecological filters during drinking water treatment - Pompei, Caroline M. Erba [UNESP]; Campos, Luiza C.; Vieira, Eny Maria; Tucci, Andréa (Elsevier, 2022)
An attractive alternative for drinking water production is ecological filtration. Previous studies have reported high removal levels of pharmaceutical and personal care products (PPCPs) by this technology. Algae and cyanobacteria play an important role in the biological activity of ecological filters. The aim of this study was to characterize and identify the community of algae and cyanobacteria in relation to its composition, density and biovolume from 22 ecological filters that received spikings of 2 μg L−1 PPCPs. For algae and cyanobacteria species, triplicate samples were collected before and 96 h after each spiking from the interface between the top sand layer of the ecological filters and the supernatant water. Results show that Chlorophyceae and Cyanobacteria were present in high numbers of taxa and abundance. The specie Lepocinclis cf. ovum (Euglenophyceae) had the highest percentage occurrence/abundance and frequency into the filters, indicating a possible tolerance by Lepocinclis cf. ovum to the concentration of selected PPCPs. Although the concentration of PPCPs did not affect the treated water quality, they did affect the algae and cyanobacteria community. No differences were detected between filters that received a single PPCP and filters that received a mixture of the six compounds. Also, changes in the composition of algae and cyanobacteria communities were observed before and 96 h after the spikings.
Keywords: Biovolume; Ecological purification; Phytoplankton; PPCPs; Slow sand filtration; Taxonomy